2015
DOI: 10.14411/fp.2015.043
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies of Neospora spp. and Toxoplasma gondii in horses from southern Italy

Abstract: Abstract:The consumption of horse meat has been epidemiologically linked to clinical toxoplasmosis in humans and neosporosis that may cause clinical illness in horses. Here we determined seroprevalence of antibodies against Toxoplasma gondii Nicolle et Manceaux, 1908 and species of Neospora Dubey, Carpenter, Speer, Topper et Uggla, 1988 in horses from Italy. Blood samples were collected from 643 apparently healthy horses from 60 farms of 51 municipalities in southern Italy. The presence of antibodies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
3
12
1
1
Order By: Relevance
“…raised in two farms in the south-western part of the study area, where outbreaks of bovine besnoitiosis were recently reported [3,4] infection, ten horses were positive to the parasite, resulting a prevalence of 3.7%; whereas no donkey showed antibodies against T. gondii. Epidemiological studies conducted in Southern Italy using IFAT reported a seroprevalence of 3% in horses [10] and 8% in donkeys [9]. A similar seroprevalence of T. gondii infection in equids (2-4%) was reported in Greece and in Switzerland;…”
Section: Accepted Manuscriptsupporting
confidence: 58%
See 1 more Smart Citation
“…raised in two farms in the south-western part of the study area, where outbreaks of bovine besnoitiosis were recently reported [3,4] infection, ten horses were positive to the parasite, resulting a prevalence of 3.7%; whereas no donkey showed antibodies against T. gondii. Epidemiological studies conducted in Southern Italy using IFAT reported a seroprevalence of 3% in horses [10] and 8% in donkeys [9]. A similar seroprevalence of T. gondii infection in equids (2-4%) was reported in Greece and in Switzerland;…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…(2.3-28%) has been reported in equids reared in Southern Italy [7,8,9,10]. In Northern Italy data are limited to T. gondii infection in horses destined for human consumption (17.6%) [11], although the presence of the parasite in this area was recently reported in other domestic and wild species [12,13,14,15].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…This was probably due to a greater probability of exposure to T. gondii oocysts in males because of the active characteristic of roosters. Many studies indicated that gender was not a risk factor for toxoplasmosis [ 1 , 13 ]. However, T. gondii change the concentration of steroid hormones in the host and enhance the susceptibility of males or females to toxoplasmosis; it was decided by the stains T. gondii [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…in [29, 30]). Recent studies in Europe have shown seropositivity rates of 1.7% in Greece [31], 10.8% in Spain [32], 3% [33] and 17.6% in Italy [34], 23% in the Czech Republic [35], 37.8% in Romania [36], and from 13 to 90% (depending on the cut-off) in France [37]. It is difficult to assess whether the reported data represent real differences in the seroprevalence of T. gondii infection or possibly reflect the use of different assays, different cut-offs for modified agglutination assays or perhaps intrinsic differences in the study samples regarding age and/or true origin of the animals.…”
Section: Discussionmentioning
confidence: 99%